First UK use of bacteriophage therapy with DAIR for chronic Staphylococcus aureus prosthetic joint infection - A. Scobie; T. Ferry; D. Roulston; S. Subbarao; T. Thai; G. Trafford; A. Cudmore; J. Miles; K. Crick; S. H. Chin; R. Lester; S. Warren; et al. (ASM Case Reports, 2026)
ABSTRACT Background Chronic Staphylococcus aureus prosthetic joint infection (PJI) remains difficult to manage when surgical revision and long-term antibiotics are not feasible. Bacteriophage therapy is emerging as a potential adjunct, though experience in orthopedic infections, particularly in the United Kingdom, is limited. Case Summary We report the first UK case of intra-articular bacteriophage therapy administered alongside debridement, antibiotics, and implant retention (DAIR) for chronic methicillin-sensitive Staphylococcus aureus knee PJI. An 81-year-old man with multiple comorbidities developed persistent infection following revision knee arthroplasty, with recurrent sinus formation despite multiple surgical washouts and prolonged suppressive antibiotics. Major revision surgery and amputation were not viable options. Following a multidisciplinary review through the UK Clinical Phage Network, targeted phage therapy was pursued as salvage treatment. Phage susceptibility testing identified an active lytic phage (ISP). The patient underwent open DAIR with intra-articular phage administration, adjunctive local antibiotics, short-course intravenous antimicrobials, and subsequent oral suppressive therapy. Two further intra-articular phage doses were administered postoperatively. Initial sinus closure occurred, but recurrence developed within 4 weeks. At 18 months, symptoms were partially improved with better mobility and reduced inflammation, though one sinus tract persisted. No significant adverse effects were observed. Whole-genome sequencing of pretreatment isolates demonstrated a predominantly ST5 S. aureus genotype with conserved biofilm-associated virulence genes and limited antimicrobial resistance in addition to clonal diversification consistent with chronic biofilm infection. Conclusion This case demonstrates the feasibility and safety of intra-articular phage therapy during DAIR in a UK setting but highlights biological, logistical, and pharmacological factors that may limit efficacy in advanced chronic PJI.